Prospective study on usefulness of sural-nerve biopsy - Saproo, Nipun; Singh, Roma (International Journal of Research in Medical Sciences, 2021)
Background: Peripheral neuropathies are a heterogeneous group of disorders, but common among patients attending neurology clinics. A systematic approach, like sural nerve biopsy, is the need of the hour, for a cost effective diagnosis. Studies have shown that nerve biopsy improves treatment in up-to 60% patients. Present study was conducted to evaluate the clinical profile and usefulness of sural nerve biopsy in peripheral neuropathy. Methods: A prospective study was conducted in the Department of Neurology in collaboration with Department of Pathology, Medanta: The Medicity, Gurugram, for a period of six months from January 2019- June 2019. Out of total 82 randomly selected patients, 43 patients were selected for nerve biopsy. Results: Mean age in the biopsy group was 45.61±19.24 years. Duration of illness was less than 1 year in 60.5% patients. In 39.5% of cases, nerve biopsies established the diagnosis and in total 77% of cases it was worthwhile. Hansen’s disease was diagnosed in 44%, CIDP in 12%, Vasculitis in 14%, and diabetes in 7% patients. Biopsy proved more diagnostic when tingling and numbness was there. Diminished DTRs was also statistically significant symptom in biopsy favoring group. Nerve biopsy in multiple mononeuropathy (65.1%) proved more beneficial than in polyneuropathy (32.6%). Similarly, motor-sensory was a predominant presentation in 28 (65.1%) patients with nerve biopsy being more valuable. Conclusions: Nerve biopsy, having a good diagnostic yield, can be a useful aid in cases with multiple mono-neuropathy. It can be the key to prevent long term neurological complications in patients.